Associations of the volume and proportion of vigorous-intensity physical activity with all-cause, cardiovascular, and cancer mortality: a systematic review and meta-analysis - Dechao Wang; Lina Wu; Lixue Yan; Huan Yang; Xiaoli Huang; Zongping Wang; Yanfei Guan (PeerJ)
Objective This study aims to systematically investigate the associations of varying volumes of vigorous-intensity physical activity (VPA) and its proportion to moderate-to-vigorous intensity physical activity (MVPA) with all-cause, cardiovascular disease (CVD), and cancer mortality. Methods The review was registered in the PROSPERO (CRD42024525067). Web of Science, Embase, and PubMed were searched from inception to March 22, 2024. Empirical studies that investigated the effects of VPA compared to light-to-moderate intensity physical activities (LMPA) on all-cause, CVD, and cancer mortality were included. Additionally, studies that reported the effects of the proportion of VPA (relative to MVPA) on these mortality risks were also included. Results In total, 20 studies were included in the analyses. A curvilinear inverse dose-response relationship was observed between the volume of VPA and all-cause, CVD, and cancer mortality. Engaging in 180 minutes of VPA per week was associated with a substantial reduction in mortality risk: 22% for all-cause mortality, 23% for CVD mortality, and 14% for cancer mortality, compared to LMPA. Further increases in VPA volume yielded only modest additional benefits. Furthermore, a U-shaped inverse dose-response relationship was observed between the proportion of VPA (relative to MVPA) and all-cause as well as CVD mortality. Compared to 0% VPA, a 37.5% VPA (relative to MVPA) was associated with the greatest reduction in all-cause mortality (HR = 0.90, 95% CI [0.88–0.93]) and CVD mortality (HR = 0.88, 95% CI [0.83–0.94]) risk, and the size of the reduction remained stable when VPA constituted 30–60% of MVPA. Conclusion Engaging in more than 180 minutes of VPA per week is associated with a substantial reduction in risks of all-cause, CVD, and cancer mortality. Maintaining VPA at 30-60% of total MVPA appears to be associated with maximal reduction in all-cause and CVD mortality risks.